The Role of Quality Management in Strengthening Teacher Professionalism: A Multi-Case Study of High-Performing Islamic Schools in Indonesia - Asnawati Asnawati; Abu Hasan Agus R (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
educational quality, particularly through enhancing teacher professionalism as a central determinant of effective teaching and learning outcomes. In the context of Islamic senior high schools, the implementation of quality management requires adaptive strategies aligned with institutional characteristics. This study aims to analyze the implementation of quality management in enhancing teacher professionalism in two leading Islamic senior high schools in Indonesia. This study employed a qualitative approach with a multi-case study design conducted at SMA Unggulan Badridduja and SMA Syekh Abdul Qodir Al-Jailani. Data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, teachers, and administrative staff. Data analysis was conducted using cross-case analysis to identify patterns, similarities, and contextual differences in the implementation of quality management practices across both institutions. The findings indicate that both schools have systematically implemented quality management components, including strategic planning, continuous professional development, and structured performance evaluation. However, differences were identified in their implementation focus. SMA Unggulan Badridduja prioritizes curriculum innovation and academic excellence, while SMA Syekh Abdul Qodir Al-Jailani emphasizes strengthening organizational culture and enhancing parental engagement in educational processes. The study concludes that effective quality management implementation significantly contributes to improving teacher professionalism, which positively impacts instructional quality and student learning outcomes. These findings highlight the importance of contextualizing quality management practices to institutional needs to achieve sustainable educational improvement.